DESIGN AND DEVELOPMENT OF DESK STUDY MULTIFUNCTIONAL IN ORDER TO SAVE SPACE USING QFD METHODE - Wilson Parulian Simatupang (Journal of Industrial Engineering Management, 2021)
Today many consumers want to own some product but other things had got in the way for one thing, it's an area of land owned by consumers. So the problem of consumers buying goods is product dimensions. That problem make consumers hesitate to buy a product. Nowadays furniture entrepreneurs, especially desk entrepreneurs, are required to make new innovations in which products are much more space efficient without eliminating the most powerful factors. To be able to design and develop the product that consumers want is done by spreading open questionnaires, then after the results have been obtained from the open questionnaires have taken a closed questionnaire. After getting the data from the questionnaire, then build a QFD (quality function deployment). After build a QFD then analysis product. The feasibility of the product is a step made to analyze whether it is worth the business product. In terms of financial value that’s IRR (Internal Rate of Return) 3,45% and positif for NPV.